The benefits of ventriculoperitoneal shunting in normal pressure hydrocephalus patients—a follow-up of three years - Gencer, Aylin H.; Schwarm, Frank P.; Nagl, Jasmin; Uhl, Eberhard; Kolodziej, Malgorzata A.; Justus Liebig University Giessen (My University, 2024)
Objective: The ventriculoperitoneal shunt (VPS) is an established approach in treating normal pressure hydrocephalus (NPH). This study aims to examine the long-term effects of VPS regarding clinical and radiological outcomes, to explore interdependencies with comorbidities and medication, and to determine a suitable opening pressure of the programmable valve. Methods: 127 patients with VPS were retrospectively evaluated. The Hakim triad along with Evans index (EI) and callosal angle (CA) were examined preoperatively and postoperatively at various time points up to over thirty-six months. Preexisting comorbidities and medication were considered. Adjustments to valve settings were documented along with symptom development and complications. Wilcoxon and paired-sample t-tests were used to analyze postoperative change. Chi-square, Eta-squared, and Pearson coefficients were used in correlation analyses. Results: Relief from individual symptoms was most prominent within the first 6 months (p < 0.01). EI and CA significantly decreased and increased, respectively (p < 0.05). Postoperative clinical and radiological improvement was largely maintained over the follow-up period. Diabetes mellitus and apoplexy correlated with surgical outcomes (p < 0.05). The median opening pressure as a function of overall symptom management was determined to be 120 mmH2O for women and 140 mmH2O for men. Conclusion: VPS is effective in treating NPH with respect to both clinical and radiological outcomes, although these two components are independent of each other. Improvement is most pronounced in short-term and maintained in the long-term. Comorbidities have significant influence on the course of NPH. The valve setting does not forecast change in radiological findings; consequently, priority should be placed on the patient’s clinical condition.
Keywords: ddc:610